Participação social nas agências reguladoras: uma análise focada na atuação da sociedade civil no processo regulatório - Artes, Joana Schmidt (2023)
This dissertation aims to study social participation in Brazilian federal regulatory agencies, focusing on the participation of civil society in the regulatory process. The focus is justified as it is understood that the Brazilian regulator is closer to economic agents, as a result of the capture problem of regulatory agencies. With that, it is exposed that the participation of civil society is generally subsidiary during the edition of normative acts by the regulatory agencies, even due to the difficulty that the general population has in making technical contributions. The need to ensure popular participation in the activities carried out by the agencies does not come from the supposed democratic deficit that these agencies would suffer, but from the Constitution guaranteeing social participation as an implicit principle that governs all state activities. In analysis of the Regulatory Agencies Law (Federal Law No. 13,848/2019) it is observed how civil society's participation in the regulatory process has had a positive impact. It is noted that the Regulatory Agencies Law, in accordance with the Constitution, prescribes the obligation of popular participation in the decision-making processes of these autarchies. However, the Law is permeated with excessively vague terms to define in which situations the adoption of social participation mechanisms would be appropriate. A possible interpretation of these devices is then presented, discussing limits and extensions to participation in agency activities. As limits, one can mention the urgent situations that would dispense with the adoption of participation institutes. On the other hand, as an extension, the possibility of carrying out public consultantions and public hearings is mentioned, not only in the rule making process, but also during the process of elaboration of planning instruments of the agencies. Bearing in mind that, for the first time in the Brazilian legal system, social participation is differentiated between consumers, users of public services and economic agents, solutions are presented to ensure greater participation of these first two groups, which make up civil society. Among these solutions, it stands out the invitation to interested parties, preferably associations representing users and consumers or, even, social organizations, to manifest themselves before the agencies' decisions, since there is a greater possibility that, through the representation, civil society can present contributions better scientifically grounded in technical debates. In addition, there is a need for agencies to improve some internal practices. Among these, the need for agencies to manifest more frequently about the contributions received, which must be done within the period determined by law; to seek new participation mechanisms that take into account both technological advances, mainly in the communication sector, as well as the vulnerability of consumers and users. The need to consolidate social participation instruments in regulatory agencies, therefore, stems not only from a constitutional and infraconstitutional imposition, but also from a readaptation of these autarchies to the current Brazilian reality and to the new trends of Administrative Law, the main one being consensualism